Patient self‐testing of white blood cell count and differentiation: A study of feasibility and measurement performance in a population of Danish cancer patients. (19th November 2019) - Otto Mattsson, Thea; Lindhart, Christina Louise; Schöley, Jonas; Friis‐Hansen, Lennart; Herrstedt, Jørn
Abstract: Objective: Patients in anticancer treatment with a known side effect of neutropenia are monitored closely with laboratory measurements of white blood cell count (WBC) and differentiation. This study sought to evaluate measurement properties and feasibility of patients' self‐testing using a point‐of‐care testing (POCT) device. Methods: A prospective feasibility and measurement study comparing the standard measurement of cancer patients' WBC and neutrophil count with POCT measurements. The study included 60 outpatients and 22 inpatients from a department of oncology at a university hospital. Results: Patients successfully conducted 106 measurements using the POCT device. 46% of the patients were >70 years. Weighted Deming regression analysis showed minimal yet significant proportional bias between methods, with POCT increasingly underestimating both total WBC and neutrophils compared with the standard method the higher the count. Over 90% of patients reported they were willing and considered themselves able to use the POCT device at home. Conclusions: The instrument can be used for self‐testing of post‐anticancer leukopenia and has sufficient measurement precision for patient risk stratification. Patients are able and willing to conduct measurements including when in a situation of acute illness. Further studies are needed to confirm safety and value within patients' own home.